High resolution facies architecture and digital outcrop modeling of the Sandakan formation sandstone reservoir, Borneo: Implications for reservoir characterization and flow simulation - Siddiqui, N.A. (Elsevier B.V., 2018)
Advances in photogrammetry have eased the acquisition of high-resolution digital information from outcrops, enabling faster, non-destructive data capturing and improved reservoir modeling. Geocellular models for flow dynamics with in the virtual outcrop in siliciclastic deposits at different sets of sandstone facies architecture remain, however, a challenge. Digital maps of bedding, lithological contrast, spatial-temporal variations of bedding and permeability characteristics make it more easy to understand flow tortuosity in a particular architecture. An ability to precisely model these properties can improve reservoir characterization and flow modeling at different scales. Here we demonstrate the construction of realistic 2D sandstone facies based models for a pragmatic simulation of flow dynamics using a combination of digital point clouds dataset acquired from LiDAR and field investigation of the Sandakan Formation, Sabah, Borneo. Additionally, we present methods for enhancing the accuracy of outcrop digital datasets for producing high resolution flow simulation. A well-exposed outcrop from the Sandakan Formation, Sabah, northwest Borneo having a lateral extent of 750 m was chosen in order to implement our research approach. Sandstone facies and its connectivity are well constrained by outcrop observations, data from air-permeability measurements, bilinear interpolation of permeability, grid construction and water vector analysis for flow dynamics. These proportions were then enumerated in terms of static digital outcrop model (DOM) and facies model based on sandstone facies bedding characteristics. Flow simulation of water vector analysis through each of the four sandstone facies types show persistent spatial correlation of permeability that align with either cross-bedded orientation or straight with more dispersion high quality sandstone (porosity 21.25â41.2 and permeability 1265.20â5986.25 mD) and moderate quality sandstone (porosity 10.44â28.75 and permeability 21.44â1023.33 mD). Whereas, in more heterolithic sandstone (wavy- to flaser-bedded and bioturbated sandstone), lateral variations in permeability show spatially non-correlated patterns over centimeters to tens of meters with mostly of low quality sandstone (porosity 3.4â12.31 and permeability < 1 mD to 3.21 mD). These variations reflect the lateral juxtaposition in flow dynamics. It has also been resulted that the vertical connectivity and heterogeneities in terms of flow are mostly pragmatic due to the interconnected sandstone rather than the quality of sandstone. Â© 2018 China University of Geosciences (Beijing) and Peking University